Lean thinking : banish waste and create wealth in your corporation - Womack, James P., 1948-; Jones, Daniel T., 1981- (New York (N.Y.) : Free press, 2003)
Lean Thinking begins by helping listeners to identify value, asking, "What does the customer really want?" instead of "What can we try to convince the customer to accept?" Lean thinkers then identify the value stream -- every step required to move a specific good or service from initial concept into the hands of the customer -- for each product and ask if each step really creates value. Those that don't -- the great majority -- are then removed, and the remaining steps are conducted in continuous flow at the pull of the customer, as the firm manages toward perfection. As a consequence, lead times, costs of all sorts, and defects shrink, while responsiveness to customer needs and selling prices increase. In an economic downturn, many companies are searching desperately for a sustainable formula for renewed growth and success. Lean Thinking is that formula -- a proven blueprint and specific action plan that will help any company stabilize its position and grow steadily while better serving its customers, employees, suppliers, and investors.
Keywords: Industrial efficiency; Lean manufacturing; Organisatieleer; Organizational effectiveness; Value added